Suspended particulate and dissolved organic carbon (POC and DOC), electron transport system (ETS) activity, derived respiration and POC fluxes in the Canary Current upwelling region - Javier Arístegui; María Fernanda Montero; Nauzet Hernández-Hernández; Iván J Alonso-González; Federico Baltar; Maria Ll Calleja; Carlos Manuel Duarte (PANGAEA, 2021)
The present data were collected from two cruises that took place in the Canary Current from September 10 to October 1, 2002 (COCA I) and from May 21 to June 7, 2003 (COCA II). The study was conducted along two zonal sections (21N and 26N) extending from the coastal upwelling to the open ocean at 26W, and focused on the epipelagic (0-200 m) and mesopelagic (200-1000 m) zones. The cruises consisted of a total of 31 hydrographic stations and 10 biogeochemical stations, half of them along each section, which were roughly equidistant. At each station seawater samples were collected at fixed depths in the biogeochemical stations every 50 m for suspended POC, DOC and ETS activity by means of a Seabird 911+ CTD, mounted on a General Oceanics rosette sampler equipped with 24 10L-Niskin bottles. Free-drifting sediment traps were deployed for 24 h at each biogeochemical station to collect sinking particles at 200 m depth.